2011
DOI: 10.1002/cne.22631
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and aging of serotonergic fibers after single and intermittent MDMA treatment in dark agouti rat

Abstract: 3,4-Methylenedioxymethamphetamine (MDMA; ecstasy) is a popular party drug known to cause selective serotonergic damage. Here we examined the long-term recovery and aging of serotonergic fibers and levels of brain-derived neurotrophic factor (BDNF) after intermittent MDMA administration (15 mg kg(-1) i.p. every 7th day for 4 weeks, MDMA ×4) and a single-dose treatment (15 mg kg(-1) i.p., MDMA ×1) in adolescent/young adult male Dark Agouti rats. After MDMA treatment, tryptophan hydroxylase-immunoreactive fiber d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…Such features have already been reported for serotonergic and cholinergic systems in normal, aging rats [7,110,77,3], as well as in the entire monoaminergic system of Zitter mutant or microenchephalic rats [106,114]. Enlarged/swollen varicosities are generated by accumulations of intra-axonal materials as a result of impaired axonal transport due to destabilization of microtubules.…”
Section: Selective Noradrenergic Axonal Degeneration In Sstr2 -/-Brainssupporting
confidence: 55%
See 1 more Smart Citation
“…Such features have already been reported for serotonergic and cholinergic systems in normal, aging rats [7,110,77,3], as well as in the entire monoaminergic system of Zitter mutant or microenchephalic rats [106,114]. Enlarged/swollen varicosities are generated by accumulations of intra-axonal materials as a result of impaired axonal transport due to destabilization of microtubules.…”
Section: Selective Noradrenergic Axonal Degeneration In Sstr2 -/-Brainssupporting
confidence: 55%
“…connections' and 'aberrant fiber clusters'/mm 2 were determined in unilateral fronto-parietal cortices as described before [3]. A detailed description of these aberrant structures is reported in the Results and Fig.…”
Section: Immunohistochemistry On Perfused Human Brainsmentioning
confidence: 99%
“…Recent studies have shown that MDMA chronically inhibits neocortical serotonin signaling in parallel with hyperthermia345 and causes deficits in prospective memory and/or social intelligence6. Animal studies have demonstrated that repeated administration of MDMA results in clusters of aberrant serotonergic fibers7 and affects the serotonergic neurotransmitter system in an association with reduced density of cerebral serotonin transporters (SERT) in the brain89. Regarding serotonergic pathway of brain, MDMA alters serotonin (5-HT), 5-HT receptors, and SERT levels910.…”
mentioning
confidence: 99%
“…Because the positive mood intensification under MDMA is brief (several hours), and the post-MDMA period of mood recovery is more prolonged (several days), the average weekly mood of Ecstasy users will often be lower than in non-users (Parrott and Lasky, 1998). Such effects are supported in the animal literature by the acute and subacute impact of MDMA on 5-HT, notably, delays in recovery of this transmitter in brain regions regulating emotion (Colado et al, 1999); and similar pattern reductions in other functional serotonergic factors, such as SERT and tryptophan hydroxylase (Adori et al, 2011). …”
Section: Discussionmentioning
confidence: 75%